Literasi Dini sebagai Fondasi Berpikir Simbolik pada Anak Usia 4–6 Tahun - Matilda Asung (Muara Aksara: Jurnal Ilmiah Multidisipliner, 2026)
Early literacy plays an important role in earlychildhood cognitive development, particularly in building symbolic thinking skills. However, early literacy is often narrowly understood as the ability to read and write, which limits its broader potential to support symbolic representation and meaning-making. This article aims to examine the role of early literacy as a foundation for symbolic thinking in children aged 4–6 years. This study employs a literature review method by analyzing various scholarly sources related to early literacy, cognitive development, and symbolic thinking in early childhood. The findings indicate that early literacy not only supports letter and sound recognition but also helps children understand symbols, develop language skills, strengthen memory, enhance reasoning, and build representational and learning readiness skills. Activities such as reading stories, playing with symbols, recognizing letters, and engaging in verbal interaction with adults effectively stimulate children’s symbolic thinking. Therefore, early literacy serves as an essential foundation for supporting overall cognitive development and symbolic thinking in early childhood.